Epitranscriptional regulation of TGF-β pseudoreceptor BAMBI by m6A/YTHDF2 drives extrinsic radioresistance - Liangliang Wang (The Journal of Clinical Investigation, 2023)
Activation of TGF-β signaling serves as an extrinsic resistance mechanism that limits the potential for radiotherapy. Bone morphogenetic protein and activin membrane-bound inhibitor (BAMBI) antagonizes TGF-β signaling and is implicated in cancer progression. However, the molecular mechanisms of BAMBI regulation in immune cells and its impact on antitumor immunity after radiation have not been established. Here, we show that ionizing radiation (IR) specifically reduces BAMBI expression in immunosuppressive myeloid-derived suppressor cells (MDSCs) in both murine models and humans. Mechanistically, YTH N6-methyladenosine RNA-binding protein F2 (YTHDF2) directly binds and degrades Bambi transcripts in an N6-methyladenosine–dependent (m6A-dependent) manner, and this relies on NF-κB signaling. BAMBI suppresses the tumor-infiltrating capacity and suppression function of MDSCs via inhibiting TGF-β signaling. Adeno-associated viral delivery of Bambi (AAV-Bambi) to the tumor microenvironment boosts the antitumor effects of radiotherapy and radioimmunotherapy combinations. Intriguingly, combination of AAV-Bambi and IR not only improves local tumor control, but also suppresses distant metastasis, further supporting its clinical translation potential. Our findings uncover a surprising role of BAMBI in myeloid cells, unveiling a potential therapeutic strategy for overcoming extrinsic radioresistance.